(untitled) (Journal of the College of Basic Education, 2022)
Each type of information has its own way of thinking. History is a social subject Part of the human sciences, one of its most important goals is the intelligent interpretation of reality, events and conflicts, and the help of The learner is able to understand his environment, realize its advantages and disadvantages, provide smart solutions to it, and acquire the ability to Inference and the study of history develops the ability to judge events and people, and accordingly the information Historicism needs a way of thinking of its own (Saada, 1986, p. 122). What is meant by the way of thinking here is: Criticism and confrontation.